PEMANFAATAN DIGITAL MARKETING BAGI USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DALAM MEMPROMOSIKAN PRODUK - rina raflina (Jurnal Cakrawala Ilmiah, 2024)
Digital marketing provides opportunities for UMKM to introduce their products more widely at a relatively more efficient cost compared to conventional marketing methods. This research aims to examine how UMKM can utilize digital platforms, such as social media, search engines and websites, to promote their products. The results of this research show that the appropriate use of digital marketing can increase the visibility and competitiveness of UMKM products in the wider market. Apart from that, implementing a good digital marketing strategy can help increase interaction with consumers, expand market reach, and increase sales and customer loyalty. Therefore, it is important for UMKM players to continue to develop skills in using digital technology to maximize market potential and achieve long-term success. Digital marketing provides the opportunity for UMKM to introduce more of their products at a relatively more economical budget compared to traditional marketing methods. The aim of this research is to find out how UMKM can use digital platforms such as websites, social media and other search engines to promote their products. The findings show that digital marketing, if used appropriately, can increase the visibility and competitiveness of products produced by UMKM in more markets. Apart from that, implementing a good digital marketing strategy can improve relationships with consumers in expanding the market to increase sales and consumer loyalty.